2014
DOI: 10.1016/j.biomaterials.2013.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Janus magnetic cellular spheroids for vascular tissue engineering

Abstract: Cell aggregates, or spheroids, have been used as building blocks to fabricate scaffold-free tissues that can closely mimic the native three-dimensional in vivo environment for broad applications including regenerative medicine and high throughput testing of drugs. The incorporation of magnetic nanoparticles (MNPs) into spheroids permits the manipulation of spheroids into desired shapes, patterns, and tissues using magnetic forces. Current strategies incorporating MNPs often involve cellular uptake, and should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 38 publications
0
77
0
Order By: Relevance
“…By incorporating magnetic nanoparticles (MNPs) into cellular spheroids, these self-assembled tissues can be aligned and patterned using magnetic force assembly [1218]. Our lab developed the Janus structure of magnetic cellular spheroids (JMCSs), which provides spatial control of iron oxide MNPs to form two distinct domains: cells and extracellular MNPs [19]. Mattix et al reported that iron oxide MNPs do not adversely affect the viability of JMCSs and that magnetic forces accelerated the fusion of JMCSs [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating magnetic nanoparticles (MNPs) into cellular spheroids, these self-assembled tissues can be aligned and patterned using magnetic force assembly [1218]. Our lab developed the Janus structure of magnetic cellular spheroids (JMCSs), which provides spatial control of iron oxide MNPs to form two distinct domains: cells and extracellular MNPs [19]. Mattix et al reported that iron oxide MNPs do not adversely affect the viability of JMCSs and that magnetic forces accelerated the fusion of JMCSs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our lab developed the Janus structure of magnetic cellular spheroids (JMCSs), which provides spatial control of iron oxide MNPs to form two distinct domains: cells and extracellular MNPs [19]. Mattix et al reported that iron oxide MNPs do not adversely affect the viability of JMCSs and that magnetic forces accelerated the fusion of JMCSs [19]. Unlike conventional tissue patterning methods, magnetic fields are physical forces used to promote active cell–cell contacts and interactions that arise from the adhesive and cohesive interactions between cells under the influence of magnetic attraction [19].…”
Section: Introductionmentioning
confidence: 99%
“…2015, 8(8): 2515-2532 implementation of MNPs-modified cells in fabrication of artificial constructs imitating vascular tissue [4], skeletal muscle tissues [5], and keratinocyte sheets [6]. Magnetic functionalization of cells was also employed in fabrication of cellular spheroids [7], which are regarded as three-dimensional building blocks in tissue engineering and a prospective tool in pharmaceutical applications (i.e., drug screening) [8] and tumor studies [9]. MNPs-modified cells were also employed for fabrication of aortic valve mimics using a magnetic levitation procedure [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental approaches based on cell-internalized magnetic nanoparticles have raised concerns regarding possible long-term toxic effects. To minimize the potential toxic effects of MNPs, several recent studies have suggested using MNPs isolated from magnetotactic bacteria [17], which are believed to be less toxic than chemically synthesized MNPs, fabrication of magnetoferritin nanoparticles, or construction of Janus magnetic cellular spheroids by concentrating nanoparticles in certain regions of spheroids, thus reducing MNPs-cell interactions [8]. Although effective, these approaches are rather complex and require time-consuming manipulation of cells or sophisticated methods of nanoparticle preparation.…”
Section: Introductionmentioning
confidence: 99%
“…15 For example, Mattix et al designed and manufactured magnetic vascular nanoparticles for rapid endothelialization to reduce the risk of restenosis. 16 Moreover, after modification with anti-CD34 antibody on the surface of a stent, the attachment of ECs was promoted greatly. 17 As a future therapeutic strategy, gene therapy has been bloomed over years.…”
Section: Feng Et Almentioning
confidence: 99%